2014
DOI: 10.1186/1758-5996-6-39
|View full text |Cite
|
Sign up to set email alerts
|

High serum phosphate and triglyceride levels in smoking women and men with CVD risk and type 2 diabetes

Abstract: BackgroundBoth low and high serum phosphate levels may be associated with morbidity and mortality from cardiovascular disease. As smoking increases risk for type 2 diabetes (as shown by dyslipidemia and hyperglycemia), we wanted to study whether smoking and type 2 diabetes were associated with serum phosphate and triglyceride levels independently from other CVD risk factors.MethodsUpon admittance to the Vindeln Health Education Centre (VHE-centre) for a four-week comprehensive lifestyle intervention, the parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 28 publications
5
26
0
Order By: Relevance
“…This was, however, expected because an association between cigarette consumption and triglyceride levels has already been reported [34][35][36][37]. This issue has been at least partially addressed by adjusting all the analyses for triglyceride levels.…”
Section: Study Limitationsmentioning
confidence: 86%
“…This was, however, expected because an association between cigarette consumption and triglyceride levels has already been reported [34][35][36][37]. This issue has been at least partially addressed by adjusting all the analyses for triglyceride levels.…”
Section: Study Limitationsmentioning
confidence: 86%
“…We found higher levels of S-P and S-TG in smokers compared to non-smokers in both women and men, and we found that these differences still existed after adjusting for age and CVD risk 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 5 factors using multiple linear regression analysis [8]. In a community study, a higher prevalence of smokers was seen in the highest quartile of serum phosphate [9,10].…”
Section: High Serum Phosphate In Smokersmentioning
confidence: 68%
“…In a previous study, we found that women who were former, current, or occasional smokers had the lowest prevalence of PD, a prevalence that differed significantly from women in the control group [8]. The disease process in PD starts several years before the first motor symptoms occur and the PD diagnosis becomes established, but the protecting effect from smoking seems to persist and to be depend on age at onset and duration of PD.…”
Section: Smoking Can Be a Protective Risk Factor For Parkinson´s Diseasementioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies [20][21][22][23][24][25][26][27][28][29][30] investigating the relationship between smoking and diabetes mellitus clarified the importance of smoking cessation for risk management of cardiovascular disease.…”
Section: Medicated People For Diabetes Mellitusmentioning
confidence: 99%